2022
DOI: 10.1155/2022/5489553
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin D Inducing Apoptosis and Autophagy through the Activation of Endoplasmic Reticulum Stress in Glioblastoma

Abstract: Saikosaponin D (SSD), a saponin derivative, is extracted from Bupleurum falcatum. It exhibits an inhibitory effect on a number of tumor cells and is relatively safe when used at therapeutic doses. However, its effects on glioblastoma multiforme (GBM) have not been fully explored. This study is aimed at investigating the cytotoxic effects of SSD in GBM cell lines. SSD induces apoptosis and autophagy by activating endoplasmic reticulum (ER) stress in GBM cells. GBM cell proliferation activity and morphology were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Furthermore, we showed that SSd attenuated cerulein‐induced pyroptosis and established the correlations between the inhibition of pyroptosis and mitigation of inflammatory injury in PACs. Actually, some other programmed cell death forms including autophagy and apoptosis have been found to be involved in the effects of SSd on cells under different pathophysiological circumstances (Liu et al, 2022; Zeng et al, 2023). Our current findings provided new insights into how SSd affected cell fate implicated in disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that SSd attenuated cerulein‐induced pyroptosis and established the correlations between the inhibition of pyroptosis and mitigation of inflammatory injury in PACs. Actually, some other programmed cell death forms including autophagy and apoptosis have been found to be involved in the effects of SSd on cells under different pathophysiological circumstances (Liu et al, 2022; Zeng et al, 2023). Our current findings provided new insights into how SSd affected cell fate implicated in disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Then, cell viability was calculated. According to the experimental results, two low-concentration TMZ groups (50 µM [T50] and 100 µM [T100]) were selected to be combined with the two concentrations (9 µM [S9] and 12 µM [S12)) of the cytotoxic effect of SSD on GBM that we studied before [22] , namely T50/S9, T50/S12, T100/S9, and T100/S12 (Table 1).…”
Section: Tmz Sensitivity Analysis and Cell Viability Assaymentioning
confidence: 99%
“…The result was rated as negative (−) when no immunolabeling was observed in target cells, weakly positive (+) when the labeling was faint, and moderately positive (+) or strongly positive (>++) when the labeling was stronger or distinctly stronger than (++). This procedure was performed as per the methods described by Guimei Liu et al in 2022 [22] .…”
Section: Immunocytochemical Stainingmentioning
confidence: 99%
“…Saikosaponin D (SSD) is a main bioactive component of the herbal medicine Radix bupleuri and possesses various pharmacological activities, such as anti‐inflammatory, anti‐cancer and metabolic regulation 8–10 . Previous reports suggested that SSA, the epimer of SSD, alleviates lipopolysaccharide (LPS)‐evoked ALI in a mouse model 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Saikosaponin D (SSD) is a main bioactive component of the herbal medicine Radix bupleuri and possesses various pharmacological activities, such as anti‐inflammatory, anti‐cancer and metabolic regulation. 8 , 9 , 10 Previous reports suggested that SSA, the epimer of SSD, alleviates lipopolysaccharide (LPS)‐evoked ALI in a mouse model. 11 Wang et al demonstrated that SSD improves mechanical ventilation‐triggered lung injury in rat models by alleviating inflammation, apoptosis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%